2012
DOI: 10.1021/ol302544s
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of 1-Iodoalkynes and Trisubstituted Alkenes from Benzylic and Allylic Bromides

Abstract: 1-Iodoalkynes are formed in moderate to high yields from readily accessible benzylic and allylic alkyl bromides by a one-pot homologation/double elimination procedure with iodoform (CHI(3)). The developed conditions include facile purification and avoid the use of an excess of triphenylphosphine (PPh(3)), as described in classical Corey-Fuchs iodoalkynylation conditions. Replacing CHI(3) with CHI(2)Cl allows the isolation of the corresponding gem-(Z)-chloro-(E)-iodoalkene in good yield and stereoselectivity. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…The controllable electrophilic and nucleophilic properties make them as dual functionalized molecules, bringing about numerous applications in chemical transformations. 1,2 Significant progress has been made in the development of synthetic approaches for the construction of 1-iodoalkynes, including iodination of metal acetylides (Scheme 1, path a), 3 iodination of propiolic acid/trialkylsilylacetylides (path b), 4,5 a two-step homologation/iodination or elimination sequence from aldehydes or benzylic bromides (path c) 6,7 and direct iodination of terminal alkynes (path d). 8 Among these methods, the direct iodination of terminal alkynes is the most appealing strategy.…”
mentioning
confidence: 99%
“…The controllable electrophilic and nucleophilic properties make them as dual functionalized molecules, bringing about numerous applications in chemical transformations. 1,2 Significant progress has been made in the development of synthetic approaches for the construction of 1-iodoalkynes, including iodination of metal acetylides (Scheme 1, path a), 3 iodination of propiolic acid/trialkylsilylacetylides (path b), 4,5 a two-step homologation/iodination or elimination sequence from aldehydes or benzylic bromides (path c) 6,7 and direct iodination of terminal alkynes (path d). 8 Among these methods, the direct iodination of terminal alkynes is the most appealing strategy.…”
mentioning
confidence: 99%
“…We found that ethynylbenzene is fully converted into (iodoethynyl)benzene within 20 minutes in the absence of an azide, under otherwise identical conditions. After filtering the reaction mixture through Celite 16 and removing the solvent, we recorded the 13 C NMR spectrum. The chemical shift of C* in the alkyne undergoes a large upfield shift, diagnostic of the formation of the 1-iodoalkyne (Table 4).…”
Section: Mechanistic Discussionmentioning
confidence: 99%
“…Traditional methods for the synthesis of 1‐iodoalkynes includes the iodination of pre‐formed metal acetylides ( path A , Scheme ), direct iodination of terminal alkynes ( path B , Scheme ) and a two‐step homologation/iodination sequence from an aldehyde (Corey‐Fuchs reaction) or benzylic bromides ( path C , Scheme ). Alternatively, they can also be prepared by the direct iodination of trimethylsilyl‐protected alkynes or halodecarboxylation of propiolic acids ( path D , Scheme ).…”
Section: Methodsmentioning
confidence: 99%